2003
DOI: 10.1021/es025688p
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Formation of Tooeleite and Mixed Arsenic(III) or Arsenic(V)−Iron(III) Gels in the Carnoulès Acid Mine Drainage, France. A XANES, XRD, and SEM Study

Abstract: The oxidation of Fe(II) in acid mine drainage (AMD) leads to the precipitation of Fe(III) compounds which may incorporate toxic elements, such as arsenic (As), within their structure or adsorb them at their surface, thus limiting their mobility. The present work provides evidence for spatial and seasonal variations of microbial activity that influence arsenite oxidation and As immobilization in the heavily contaminated AMD from the Carnoulès mine, Gard, France ([As III] = 80 to 280 mg x L(-1) in the acidic spr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
200
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(216 citation statements)
references
References 23 publications
12
200
3
1
Order By: Relevance
“…In studies similar to the ones we present here, A. ferrooxidans has been cultured from AMD-impacted sediments , but was subsequently shown in culture-independent studies to comprise a minor fraction of Fe(II)OB-related phylotypes (Bruneel et al, 2006). The work presented here and by others suggest that organisms other than A. ferrooxidans and L. ferrooxidans may play a prominent role in oxidative precipitation of dissolved Fe(II) from AMD Hallberg and Johnson, 2003;Morin et al, 2003;Bruneel et al, 2006). Hallberg and Johnson (2003) point out that the pH of the of AMD-impacted systems may influence the composition of Fe(II)OB communities, with relatively low pH (o3.0) favoring the growth and activity of A. ferrooxidans and L. ferrooxidans, and relatively high pH (43.0) favoring the growth and activity of 'moderately acidophilic' Fe(II)OB that are phyolgenetically related to organisms that we detected in the GB and FR systems.…”
Section: Abundance and Activity Of Fe(ii)ob In The Gb And Fr Systemssupporting
confidence: 75%
“…In studies similar to the ones we present here, A. ferrooxidans has been cultured from AMD-impacted sediments , but was subsequently shown in culture-independent studies to comprise a minor fraction of Fe(II)OB-related phylotypes (Bruneel et al, 2006). The work presented here and by others suggest that organisms other than A. ferrooxidans and L. ferrooxidans may play a prominent role in oxidative precipitation of dissolved Fe(II) from AMD Hallberg and Johnson, 2003;Morin et al, 2003;Bruneel et al, 2006). Hallberg and Johnson (2003) point out that the pH of the of AMD-impacted systems may influence the composition of Fe(II)OB communities, with relatively low pH (o3.0) favoring the growth and activity of A. ferrooxidans and L. ferrooxidans, and relatively high pH (43.0) favoring the growth and activity of 'moderately acidophilic' Fe(II)OB that are phyolgenetically related to organisms that we detected in the GB and FR systems.…”
Section: Abundance and Activity Of Fe(ii)ob In The Gb And Fr Systemssupporting
confidence: 75%
“…This natural process of attenuation seems to be mainly due to microbial metabolism, leading to the oxidation of iron and arsenic into Fe(III) and As(V), and their co-precipitation with sulfur. In addition, laboratory experiments suggest that bacteria belonging to Thiomonas or Acidithiobacillus genera are involved in this process in situ Casiot et al, 2003;Duquesne et al, 2003;Morin et al, 2003;Egal et al, 2009). However, 16S-based community analyses have revealed that other genera are present in this ecosystem (Duquesne et al, 2003(Duquesne et al, , 2008Bruneel et al, 2003Bruneel et al, , 2006Bruneel et al, , 2008Bruneel et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral was 3 formed in the waste dumps from primary granular pyrite and arsenopyrite minerals 4 which were disseminated in catogenic quartz diopside ores. The mineral has also been 5 found in arsenic-bearing acid mine drainage at Carnoulès creek, France [2,3] and in 6 the acid hydrometallurgy wastes in São Bento gold mine, Brazil [4]. The valance of 7 arsenic in Tooeleite was corrected from +5 to +3 recently, as determined by Morin and 8 Nishimura et al, [1,3].…”
Section: Introductionmentioning
confidence: 95%
“…The mineral tooeleite Fe 6 (AsO 3 ) 4 SO 4 (OH) 4 ·4H 2 O was discovered at the U.S. 2 Mine, Tooele Country, Utah in 1991 by Cesbron and Williams [1]. The mineral was 3 formed in the waste dumps from primary granular pyrite and arsenopyrite minerals 4 which were disseminated in catogenic quartz diopside ores.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation